Beyond Painkillers: A Meta-Analysis of Non-Pharmacological Approaches for Managing Dysmenorrhea Symptoms - Rabia Wahdah (Archives of The Medicine and Case Reports, 2024)
Dysmenorrhea, commonly known as painful menstruation, is a highly prevalent gynecological condition affecting millions of women globally. While pharmacological interventions offer temporary relief, they often come with undesirable side effects. Non-pharmacological approaches present a potentially safer and more sustainable alternative for managing dysmenorrhea symptoms. A comprehensive search of electronic databases, including PubMed, Scopus, and Web of Science, was conducted to identify randomized controlled trials (RCTs) published between 2014 and 2024 that investigated the effectiveness of non-pharmacological interventions for dysmenorrhea. The primary outcome was pain intensity reduction, while secondary outcomes included quality of life, absenteeism, and medication use. Data were pooled using a random-effects model, and standardized mean differences (SMDs) were calculated. Six RCTs met the inclusion criteria, encompassing a total of 600 participants. The non-pharmacological interventions evaluated included aerobic exercise, yoga, acupuncture, transcutaneous electrical nerve stimulation (TENS), heat therapy, and relaxation techniques. The pooled analysis revealed significant reductions in pain intensity across all interventions compared to control groups (SMD = -2.00, 95% CI: -2.39 to -1.61, p < 0.001). Aerobic exercise and yoga demonstrated the largest effect sizes (SMD = -2.5 and -2.5, respectively). Significant improvements were also observed in quality of life, absenteeism, and medication use. Non-pharmacological approaches, particularly aerobic exercise and yoga, are effective in managing dysmenorrhea symptoms. These findings strongly support the integration of non-pharmacological interventions into clinical practice as a first-line or adjunctive treatment option for dysmenorrhea.